2014
DOI: 10.1016/j.neuron.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Activity in Neurons and Glia with a Polr2a-Based and Cre-Dependent GCaMP5G-IRES-tdTomato Reporter Mouse

Abstract: SUMMARY New strategies for introducing genetically encoded activity indicators into animal models facilitate the investigation of nervous system function. We have developed the PC::G5-tdT mouse line that expresses the GCaMP5G calcium indicator in a Cre-dependent fashion. Instead of targeting the ROSA26 locus, we inserted the reporter cassette nearby the ubiquitously expressed Polr2a gene without disrupting locus integrity. The indicator was tagged with IRES-tdTomato to aid detection of positive cells. This rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 50 publications
7
109
4
1
Order By: Relevance
“…1E) and a greater number of signals ( Fig. 1D) than endfeet or somata, comparable to previous reports with other calcium indicators and in other brain regions (Shigetomi et al 2013;Gee et al 2014;Kanemaru et al 2014;Otsu et al 2015;Srinivasan et al 2015;Tang et al 2015). A previous study has also detected three different populations of GCaMP6s peaks in astrocytes: single peaks, multi peaks, and plateaus (Bonder and McCarthy 2014).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…1E) and a greater number of signals ( Fig. 1D) than endfeet or somata, comparable to previous reports with other calcium indicators and in other brain regions (Shigetomi et al 2013;Gee et al 2014;Kanemaru et al 2014;Otsu et al 2015;Srinivasan et al 2015;Tang et al 2015). A previous study has also detected three different populations of GCaMP6s peaks in astrocytes: single peaks, multi peaks, and plateaus (Bonder and McCarthy 2014).…”
Section: Discussionsupporting
confidence: 91%
“…We also found that somata, processes and endfeet had a similar mean signal onset (~15 seconds), though peaks occurred earlier after the start of stimulation. Unlike Gee et al (2014), we did not observe similar somata and process signal amplitudes (Fig. 4D).…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…This inspiration also explains the ambitious focus on a million neurons. Obviously, research can benefit tremendously from techniques for recording up to a thousand neurons (Dombeck et al, 2010;Gee et al, 2014;Ghosh et al, 2011;Heys et al, 2014;Sheffield and Dombeck, 2014), and further benefits will also arise from recording tens of thousands of neurons or hundreds of thousands of neurons.…”
Section: Introductionmentioning
confidence: 99%